Determination of genomic N3‐methylthymidine in human cancer cells treated with nitrosamines using capillary electrophoresis with laser‐induced fluorescence. Issue 11 (27th February 2019) - Krais, Annette M.; Kliem, Christian; Arlt, Volker M.; Schmeiser, Heinz H.
Abstract: Methylating substances alter DNA by forming N3‐methylthymidine (N3mT), a mutagenic base modification. To develop a sensitive analytical method for the detection of N3mT in DNA based on capillary electrophoresis with laser‐induced fluorescence detection (CE‐LIF), we synthesized the N3mT‐3'‐phosphate as a chemical standard. The limit of detection was 1.9 amol of N3mT, which corresponds to one molecule of N3mT per 1000 normal nucleotides or 0.1%. With this method, we demonstrated that the carcinogenic nitrosamine N'‐nitrosonornicotine (NNN) induced N3mT in the human lung cancer cell line A549. Treatment with NNN also caused an elevated degree of 5‐hydroxymethylcytidine (5hmdC) in DNA, while the methylation degree (i.e. 5‐methylcytidine; 5mdC) stayed constant. According to our data, NNN could, via yet unknown mechanisms, play a role in the formation of N3mT as well as 5hmdC. In this study we have developed a new sensitive analytical method using CE‐LIF for the simultaneous detection of the three DNA modifications, 5mdC, 5hmdC and N3mT.